Analisis Kampanye TikTok “BFI Senyum Ramadhan” Sebagai Pembangun Brand Awareness di BFI Finance - Francesca, Molly; Utami, Lusia Savitri Setyo (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
Today, many companies are turning to digital marketing. Promotions are also carried out through social media such as Tik Tok. Tik Tok as a social media is experiencing rapid development. According to statistics, there are 22.2 million active Tik Tok users in Indonesia. This makes Tik Tok a company promotion medium, one of which is the financing company BFI Finance. This company once held a Tik Tok campaign